(untitled) (Research, Society and Development, 2022)
Digital technologies have been increasingly present in society, and, with this, it is possible to think about their influences on teaching and learning. In this perspective, this article aims to glimpse the current scenario of the use of digital technologies for the teaching of proportionality, an essential concept to understand several subjects of mathematics and science, through a Systematic Literature Review (RSL). For the elaboration of this study, a bibliographic analysis was carried out using Google Scholar, Capes Periodicals, RENOTE (New Technologies Magazine in Education) and BOLEMA (Mathematics Education Bulletin) as databases. Overall, it is concluded that the use of digital technologies contributes to a diversity of representations and visualizations of situations that involve proportional reasoning, helps in meaning, creates a creative and investigative environment, making the construction of mathematical knowledge to be done by the student.